2017
DOI: 10.1002/app.44929
|View full text |Cite
|
Sign up to set email alerts
|

The combination of expandable graphite, organic montmorillonite, and magnesium hydrate as fire‐retardant additives for ethylene–propylene–diene monomer/chloroprene rubber foams

Abstract: The fire retardancy and flame-retardant mechanism of expandable graphite (EG), organic montmorillonite (OMMT), and magnesium hydrate (MH) in ethylene-propylene-diene monomer/chloroprene rubber (EPDM/CR) foams were investigated. The results indicated that the combination of EG and OMMT remarkably improved the fire-retardant property compared to the control samples, and better fireproof performance was achieved when MH was used as the third coretardant unit. The structure of the obtained EPDM/CR/OMMT composites … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 35 publications
(38 reference statements)
0
7
0
Order By: Relevance
“…However, the carbon residue surface of UPR‐1‐4 and UPR‐1‐6 samples formed a honeycomb‐like structure after combustion, and significant increase of carbon residue . This suggested that continuous and cohesive stable carbon layer can effectively prevent the transfer of combustible gas and heat between condensed phase and gas phase, thereby improving the flame retardancy of composite materials …”
Section: Resultsmentioning
confidence: 99%
“…However, the carbon residue surface of UPR‐1‐4 and UPR‐1‐6 samples formed a honeycomb‐like structure after combustion, and significant increase of carbon residue . This suggested that continuous and cohesive stable carbon layer can effectively prevent the transfer of combustible gas and heat between condensed phase and gas phase, thereby improving the flame retardancy of composite materials …”
Section: Resultsmentioning
confidence: 99%
“…Notably, the fastest decomposition temperatures of MBPFs in this second stage were remarkably increased by about 40 °C in relation to that of BPF. These phenomena indicated that MMT played an important role on the second degradation step, directly slowing down the escape of degraded compounds and the diffusion of oxygen [61].…”
Section: Resultsmentioning
confidence: 99%
“…The synergistic effects of EG, montmorillonite, and magnesium hydroxide (MH) flame retardancy within the ethylene-propylene-diene monomer/ chloroprene rubber (EPDM/CR) were found and investigated. 28 A significant synergy was also observed in EG with MH in the EVA composites with flame retardancy. 29 Combining EG with other additives is suggested to reduce the total additive amount relative to the use of only one flame retardant.…”
Section: Introductionmentioning
confidence: 90%
“…For instance, Tang et al reveals that EG has a synergistic effect with ammonium polyphosphate as well as the red phosphorus within the flame-retardant high-density polyethylene/ethylene vinyl acetate (HDPE/EVA). The synergistic effects of EG, montmorillonite, and magnesium hydroxide (MH) flame retardancy within the ethylene-propylene-diene monomer/chloroprene rubber (EPDM/CR) were found and investigated . A significant synergy was also observed in EG with MH in the EVA composites with flame retardancy .…”
Section: Introductionmentioning
confidence: 99%